Design of a solar-driven TiO2 nanofilm on Ti foil by self-structure modifications1. Issue 52 (10th June 2015) - Liu, Yan; Mu, Kangsheng; Zhong, Jiandan; Chen, Keni; Zhang, Yanzong; Yang, Gang; Wang, Lilin; Deng, Shihuai; Shen, Fei; Zhang, Xiaohong
<x xml:space="preserve">Abstract</x> A novel solar-driven VO–N–TiO2 (A/R) nanofilm was designed. Its optical absorption can cover the ultraviolet, visible and near-infrared region.